Maternal Gatekeeping Scale for infancy period (0–24 months) adaptation into Turkish: Mother and Father Form - Ergin, Fatma Elif; Demirbaş, Müberra (Frontiers in Psychology, 2024)
This research aimed to adapt the Maternal Gatekeeping Scale into Turkish for use with infants and to evaluate its validity and reliability with parents. The study employed a descriptive survey model, a quantitative research approach. Participants were selected using criterion sampling, a purposeful sampling technique. The study sample included 305 mothers and 209 fathers with infants aged 0-24 months, who are married, living together, and agreed to participate. The data in the study were collected with the "Demographic Information Form" and "Maternal Gatekeeping Scale" created by the researcher. Confirmatory factor analysis was performed for the construct validity of the Maternal Gatekeeping Scale-Mother Form and Maternal Gatekeeping Scale-Father Form. The internal consistency reliability coefficient of the Maternal Gatekeeping Scale-Mother Form was 0.76; the control sub-dimension was 0.75, the encouragement sub-dimension was 0.81, and the obstacle sub-dimension was 0.76. The internal consistency reliability coefficient of the Maternal Gatekeeping Scale-Father Form was 0.87; the control sub-dimension was 0.83, the encouragement sub-dimension was 0.87, and the obstacle sub-dimension was 0.87. In order to calculate item discriminations, 27% lower-upper groups were formed and independent sample t-test was applied to these groups. Item-total correlation values were calculated to determine the relationship between each item in the scale and other items. The findings of this study demonstrate that both the Mother and Father Forms of the Maternal Gatekeeping Scale are valid and reliable tools for assessing maternal gatekeeping among parents with infants in Türkiye. The adaptation of this scale represents a significant advancement in the field of maternal gatekeeping during infancy. It is anticipated that this adapted scale will serve as a foundational resource for future research, facilitating the exploration of determinants and consequences associated with maternal gatekeeping in infancy.